Augmenting the usability of parallel coordinate plot: The polyline glyphs. (April 2018) - Opach, Tomasz; Rød, Jan Ketil
Polyline glyphs are minimized thumbnails of polylines from parallel coordinates. Since such glyphs may augment the usability of parallel coordinates, the authors investigate whether there are benefits to be derived from using polyline glyphs that are dynamically linked to parallel coordinates as opposed to the use of the latter visualization technique alone. They also identify user tasks that can be effectively solved if parallel coordinates dynamically linked to polyline glyphs are used. This study adds to the body of previous work a discussion on the features of the polyline glyphs that facilitate the exploration and understanding of multivariate data. Moreover, the authors conduct an empirical study in which parallel coordinates dynamically linked to polyline glyphs are used to solve four tasks. The main finding is that polyline glyphs can facilitate a better insight into the similarities between the multivariate signatures of data items and information acquisition if visual clutter hinders the use of parallel coordinates. The study also reveals that if visual clutter does not occur in parallel coordinates and the polylines from the latter can be differentiated, individuals tend not to use polyline glyphs to study multivariate signatures.